Exercise and Lymphatic System - Oktay Cakmakcı; Ali Tatlıcı (Selcuk University, 2021)
The human body has two main circulatory systems, the blood and lymphatic systems. Although both systems share many functional, structural and anatomical similarities, the two vascular systems have many differences in science and medicine. Although the blood vascular system has been studied extensively and extensively for a long time, the lymphatic system has been seen as secondary to the blood vascular system and has been considered less important. Although studies in this area have increased, the lymphatic system has not been a physiological system that has received great attention in the sports medicine literature, and misinformation has been derived and comments have been made about this area. The aim of this study is to reveal the effects of exercise on the lymphatic system and to explain its possible mechanisms of action.